Environmental drivers of taxonomic, functional and phylogenetic diversity (alpha, beta and gamma components) in estuarine fish communities. (19th November 2017) - Teichert, Nils; Lepage, Mario; Chevillot, Xavier; Lobry, Jérémy
Abstract: Aim: We applied a diversity partitioning approach to identify the influence of multiple environmental factors on taxonomic, functional and phylogenetic diversity of estuarine fish assemblages at different spatial scales. Our aim was to determine (1) how variation in γ‐diversity (estuary scale) is supported by changes in α‐ (local scale) and β‐components (dissimilarity between these two scales) for the three diversity facets and (2) how these diversity measures are related to biogeographic, hydroclimatic, marine, estuarine and land cover conditions. Location: French estuaries, North East Atlantic. Taxon: Fish communities. Methods: Fish assemblages were sampled using standardized beam trawl surveys in 32 estuaries during spring and autumn (period 2005–2016). The Rao's quadratic entropy was used to decompose the γ‐diversity into α‐diversity and β‐diversity. For the three diversity facets, we used linear mixed models (LMMs) to determine the strength of the relationships between α‐, β‐ and γ‐diversities. Then, LMMs were applied to identify which environmental factors were the best predictors of diversity patterns. Results: Variability in γ‐diversity is better explained by β‐diversity than by local (α‐) diversity for the three diversity facets. The relationship between γ‐ and α‐diversity revealed a saturation effect for both taxonomic and phylogenetic indices. The influence of the five categories of explanatory variables differed depending on the diversity facet and component. We found that marine conditions were the primary drivers of phylogenetic and functional α‐diversity, whereas β‐diversity was mainly influenced by estuarine characteristics. LMMs also evidenced a role of biogeographic, hydroclimatic and land cover conditions on β‐diversity. Main conclusions: Our results support the statement that fish diversity is chiefly supported by changes in species composition along estuarine gradients, while functional dissimilarity is limited in space and time. Although diversity is influenced by numerous environmental factors, the ecological connection with the marine ecosystem appears as a key component to promote local diversity.